Expanding Pharmacist Services in Québec: A Health Reform Analysis of Bill 41 and its Implications for Equity in Financing Care - Renée Carter; Amélie Quesnel-Vallée (McMaster University Library Press, 2014)
On 8 December 2011, Québec's Minister of Health and Social Services amended the province's Pharmacy Act by introducing Bill 41 to expand pharmacists' role in patient care. Québec is the only Canadian province with a legal mandate for prescription drug insurance coverage for all residents, with public coverage offered only to those who do not have access to private health insurance through their employer. Bill 41 aims to increase access to health care and reduce physician wait times by extending the scope of pharmacist services to mirror that of physicians (e.g., modify the form of the medication and its dosage). The reform is currently pending due to disputes between the Ministry of Health and Social Services and the Quebec Association of Pharmacy Owners over remuneration for pharmacists. Should Bill 41 come into force, it is unclear whether the expansion of pharmacists' roles, which in principle would duplicate physician services, should be considered part of the public basket of medically necessary care. Current negotiations suggest that only those with public coverage will also be covered for expanded services thereby placing equity of finance for those with private insurance in question.   Le 8 Décembre 2011, le ministre de la Santé et des Services sociaux du Québec a modifié la Loi sur la pharmacie en introduisant le projet de loi 41 à élargir le rôle des pharmaciens dans les soins aux patients. Le Québec est la seule province canadienne avec un mandat légal pour la couverture d'assurance-médicaments pour tous les résidents avec la couverture publique offerte uniquement à ceux qui n'ont pas accès à l'assurance-maladie privée par leur employeur. Le projet de loi 41 vise à accroître l'accès aux soins de santé et réduire les temps d'attente chez le médecin en élargissant le champ des services pharmaceutiques pour refléter ceux des médecins (ex: modifier la forme du médicament et son dosage). La réforme est actuellement en cours en raison de différends entre le ministère de la Santé et des Services sociaux et l'Association québécoise des pharmaciens propriétaires par rapport à la rémunération des pharmaciens. Si le projet de loi 41 entre en vigueur, il est difficile de prévoir si l'expansion de service des pharmaciens devrait être considérée comme faisant partie du panier de services publics de soins médicalement nécessaires. Les négociations en cours suggèrent que seulement ceux avec la couverture publique seront également couverts pour les nouveaux services plaçant ainsi l'équité du financement pour ceux qui ont une assurance privée en question.